Investigation of Treg in Pediatric Acute Lymphocytic Leukemia Patients during Chemotherapy Stages and Relapse - Mohammed, Zainab J.; Humoud, Majid N.; Zughair, Maha K.; Salait, Sadeq K. A. A. (Scientific Journal of Medical Research, 2023)
A cross-sectional case-control study has been carried out on Treg cells in pediatric acute lymphoblastic leukemia (ALL) patients admitted to Al-Basrah Children Teaching Specialty Hospital from November 2022 to May 2023. A total number of 70 patients (25 newly diagnosed, 12 relapse, 21 during induction, and 12 during consolidation chemotherapy) were enrolled, aged 2 to 14 years, along with 54 healthy controls who were the same age and gender as the study. Blood samples were collected from all participants for flow cytometer applied to study Treg cell markers. The results of the current study showed that the highest percentage of ALL patients was in the age group of 2 to 5 years 54.3% followed by age group 6 to 12 years 41.4%, whereas the lowest percentage was in patients older than 12 year 4.3% (p-value 0.802). The p-value was considered significant if it is ? 0.05 and highly significant if ? 0.001. Regarding the flow cytometry analysis results for CD3, CD4 and CD25, ALL patients had a significantly higher mean of these markers than the control group (p-value ? 0.005). A slightly higher level CD4 was noted in new cases compared to relapse cases, and induction and consolidation (p = 0.080). The results of Treg levels cells in relapse, induction, consolidation and new diagnosis cases. On the other hand, demonstrate higher levels in the relapse group, with highly significant differences for the two parameters: CD3–CD25 (p ? 0.005). The level of CD25 displayed a highly significant difference when comparing induction with consolidation (p ? 0.005). From this study, we conclude that the immunological marker (CD 25) specifically provided the most highly significant value as immunosuppression parameters in all patients, whereas chemotherapy represents the key risk factor for immunosuppression in all patients varies significantly among chemotherapy stages, with consolidation having the most impact. This effect may be due to the high dose of MTX. Background: T regulatory cells (Tregs) are immunosuppressive cells that can be divided into numerous subsets. Tregs comprise a small but heterogeneous population, which the phenotype may identify as CD3+CD4+CD25+. They play a crucial role in the preservation of immunological homeostasis and self-tolerance. They also play important roles In the control of cancer immunity. Tregs may also be important in acute leukemia. Patients and Methods: A7 0 blood samples of both sexes with the age range 2 to 14 years old were collected from patients with ALL. Additionally, this investigation included 54 healthy controls included in CD3, CD4 and CD25 expression on leukemic blast cells were assessed using flow cytometry. Results: Increased values of CD3+CD25+ T cells were observed in children with all in comparison to healthy controls with significant differences in the markers for Tregs (mean ± SD, 14.971 ± 11.06 vs. 5.680 ± 2.96 pg/mL) (p <0.05). Following these findings, significant differences in the levels of CD25 was higher in consolidation than in the induction chemotherapy stage (mean ± SD, 17.657 ± 13.890 vs. 5.100 ± 5.1438) pg/mL (p <0.05), children with all were also found to have significantly higher levels of CD4 in the current study when compared to healthy controls (mean ± SD, 29.261 ± 13.828 vs. 28.3465 ± 11.17146) pg/mL (p <0.05), Table 2. According to the chemotherapy stage there were significant significant differences in the levels of CD25 in the relapse state, which was higher than the chemotherapy stage for new diagnosis (mean ± SD, 22.185 ± 15.148 vs. 13.649 ± 5. 83) pg/mL (p <0.05). A further finding was that the frequency of lymphoblast that expresses CD25 was considerably higher in the high-risk group compared to the standard risk group (mean ± SD, 15.75 ± 4.74 vs. 7.92 ± 1.012) pg/mL (p <0.05) Table 3. Conclusion: Chemotherapy represents the interested immunosuppression risk factor in ALL patients. There is a significant variation among chemotherapy stages in ALL patient immunosuppression. Consolidation represent the high influence on ALL patient in immune suppression may be related to the high dose of MTX.